Why Instrument Needs to be Revised? An Experience in Developing Digital Creativity Instrument with The Expert Judgement - Sari, Puji Novita; Siswandari, Siswandari; Sangka, Khresna Bayu (Fakultas Ekonomi, Universitas Negeri Semarang, 2023)
Creativity plays a crucial role in 21st-century learning, particularly in its integration with technology. The fusion of digital technology and creativity forms the emerging domain known as digital creativity. This study aimed to assess the instrument development stages of digital creativity, describe the creative products produced by students, and identify the ranking indicators of digital creativity. The research design involved the development of a digital creativity assessment instrument for accounting students, employing quantittaive descriptive research. The research subjects consisted of five experts and 177 accounting students. Data collection techniques included the Planel Expert Judgment and student performance assessments. Data analysis techniques involved Aiken's V and Consistency Reliability using the Inter-Rater Reliability, which employs the Interclass Correlation Coefficient (ICC). The results revealed that digital creativity intrument in this study was adopted and developed from Cropley Cropley (2008), Guan et al. (2021), Haller et al. (2011) and Canina Bruno (2021). The value of V and ICC values for the research instrument, focusing on instructions, language use, and content, were accepted with revisions. Similarly, the V and ICC values for the 29 indicators/items assessing digital creativity were accepted with revision. This indicate that the instrument is well-suited for measuring digital creativity, given its strong validity and reliability. Among the digital creativity indicators, the highest and lowest rangkings were associated with ethical and sustainable learning and convincingness. The three most frequently used applications by students are Capcut, Canva, and Microsoft PowerPoint.